Diagnosis and Management of Fetal Growth Restriction - Theophany Margareta Kurniawan; Pratiwi Anggraini; Meilisva Audila Anggraini (Jurnal Biologi Tropis, 2023)
Fetal Growth Restriction (FGR) or Intrauterine Growth Restriction (IUGR) is one of the complications in pregnancy that is quite common, especially in developing countries, which is one of the contributors to neonatal mortality and morbidity rates. This literature review aims to provide related information, so that proper diagnosis and management can be carried out to reduce fetal morbidity and mortality rates. We searched from online databases and used review articles, research, guidelines from professional organizations, such as POGI from Indonesia, ACOG from the USA, and RCOG from the UK. Risk factor assessment and examination of fundal height can be the first steps in diagnosing IUGR. If suspicion is found, ultrasound (USG) and Doppler velocimetry can be performed. IUGR management mostly works in influencing the vasodilation of the placenta as the most common cause of IUGR events. Fetal Growth Restriction can be diagnosed immediately by screening for risk factors in pregnant women.